2018
DOI: 10.1016/j.jcjd.2017.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Mental Health

Abstract: The experience of living with diabetes is often associated with concerns specific to the illness and can cause conditions, such as diabetes distress, psychological insulin resistance and the persistent fear of hypoglycemic episodes.• A wide range of psychiatric disorders, including major depressive disorder, bipolar and related disorders, schizophrenia spectrum and other psychotic disorders, anxiety disorders, sleep disorders, eating disorders and stress-related disorders are more prevalent in people with diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 227 publications
(203 reference statements)
2
77
0
2
Order By: Relevance
“…Besides, “psychological insulin resistance”, when adding insulin to a regimen, and “fear of hypoglycaemia”, are also two well-documented psychological effects in adults with diabetes. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Besides, “psychological insulin resistance”, when adding insulin to a regimen, and “fear of hypoglycaemia”, are also two well-documented psychological effects in adults with diabetes. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Psychological and social problems can impair the individual's (11,(197)(198)(199)(200)(201) or family's (200) ability to carry out diabetes care tasks and therefore potentially compromise health status. There are opportunities for the clinician to routinely assess psychosocial status in a timely and efficient manner for referral to appropriate services (202,203). A systematic review and metaanalysis showed that psychosocial interventions modestly but significantly improved A1C (standardized mean difference -0.29%) and mental health outcomes (204).…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…Few studies have examined the daily life of people with both conditions, including their illness management and treatment practices. Moreover, most research into diabetes and mental illness has focused on both type 1 and type 2 diabetes and common mental disorders, such as depression, rather than on the study of type 2 diabetes or severe mental illness specifically [17,18]. However, treatments and effective self-management practices for type 1 and type 2 diabetes differ in many aspects [19,20].…”
Section: Introductionmentioning
confidence: 99%